Hubungan Penggunaan Obat Nyamuk dalam Rumah Tangga dengan Kejadian ISPA pada Balita di Puskesmas Sibela Surakarta - Syahidah, Sumayyah; ., Sumardiyono; Hikmayani, Nur Hafidha (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Morbidity and mortality due to acute respiratory infection (ARI) in children under five years old is high. Contributing factors include air pollution caused by domestic use of mosquito coils and spray. Hazardous chemicals in both mosquito coils and spray can iritate respiratory tracts, thereby putting children at higher risk for infection. This research aims to examine whether domestic use of mosquito coils and spray is associated with the prevalence of ARI among children under five years at Puskesmas Sibela Surakarta. Methods: This was an observational study using case control design conducted from March to April 2012 at Puskesmas Sibela Surakarta. Forty subjects were sampled using fixed-disease sampling method. Parents of case group (20 children with ARI) and control group (20 children without ARI) were interviewed and asked to fill out specific questionnaires. Data were analyzed using Ï2 test and odds ratio. Results: Twelve children with ARI were exposed to mosquito coils and spray at home. History of mosquito coils and spray exposure at home were only found in two children without ARI. Statistical analyses showed a significant relationship between ARI in children and domestic use of mosquito coils and spray (OR = 13,5, 95% CI 2,4 to 74,9, p = 0,001). Conclusions: There was a significant relationship between domestic use of mosquito coils and spray with prevalence of ARI among children under five years at Puskesmas Sibela Surakarta. Compared to children who lived in a house not using mosquito coils and spray, those who were exposed to mosquito coils and spray at home had 13.5 times higher the risk to get ARI. Keywords: ARI, Children Under Five Years, Mosquito Coils and Spray.Â